PENGONTROLAN KUALITAS PRODUK MENGGUNAKAN METODE DIAGRAM KONTROL MULTIVARIAT np (Mnp) DALAM USAHA PENINGKATAN KUALITAS (Studi Kasus di PT Coca-Cola Amatil Indonesia (CCAI) Semarang) - Nonik Brilliana Primastuti; Sudarno Sudarno; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
The industrial revolution was mark the beginning of the rise of industrial in the world. Moreover, in this globalization era, a lot of industry popping up especially those industries in Indonesia with many of those industries would emerge also thight competition. Each company must be trying to superior to that of its products so that each company will always improve the quality of their products in various ways so that the product can deportment in the market. One way of improving the quality of by doing quality control on each of its products. There are many method of conducting control quality. One method used is multivariate np chart. Multivariate np chart usually used for nonconforming units. Based on the results of this research, it is found that the production process in phase I namely from January to February in a state of controlled so that the parameters in the production process phase I can be used in the production process phase II, while to the process of the production phase II there are several observations that are out-of-control so that the production phase II in a state of uncontrolled.